Empowerment Is Key? How Perceived Political and Critical Digital Media Literacy Explain Direct and Indirect Bystander Intervention in Online Hate Speech - Magdalena Obermaier; Ursula Kristin Schmid; Diana Rieger (Social Media + Society)
Hate speech is widespread in digital media, and such incidents can harm individuals and fuel hostile discourses. Therefore, understanding the factors that shape bystander intervention is crucial. Despite frequent calls for more research, there is a need for greater understanding of how perceived political and digital media literacy are related to the frequency of various forms of online bystander intervention, such as counter-speech or reporting. Based on a national online survey of German citizens ( N  = 2,691), we investigated how perceived political and digital media literacy of individuals with prior experience in addressing online incivilities ( n  = 672) relates to (private and public) direct and indirect forms of intervention against online hate speech. The results indicate that a sense of empowerment regarding digital media content particularly increases direct, public interventions, such as uttering counter-speech.